Ecological Assessment Of Plankton Community And Affects Of Alien Species In The Southwestern Caspian Sea - Khoughani, Siamak Bagheri (2012)
The Caspian Sea ecosystem, with its high level of endemic taxa has suffered from anthropogenic pollution, changes in the quantity of nutrients, and the effects of invasive species since the 1980s. To study the temporal changes in phytoplankton and zooplankton communities, seasonal surveys were undertaken at 12 stations in the southwestern Caspian Sea from 1996 to 2010. Among 158 phytoplankton species identified, the dominant species were the diatoms Thalassionema nitzschioides, Dactyliosolen fragilissimus, the dinoflagellate Prorocentrum cordatum, and the cyanophyte of genus Oscillatoria.